Association of Neutrophil to Lymphocyte and Platelet To Lymphocyte ratio with Blood Glucose Regulation in Type 2 Diabetes Patients - Sualeha Ahmed, Muhammad Ali Khalid, Muqadas Munir, Imran Arshad, Muhammad Maaz (Journal of Rawalpindi Medical College, 2021)
INTRODUCTION: Diabetes is characterized by chronic hyperglycemia with disturbances of carbohydrate, protein and lipid metabolism. Disorders of lipid metabolism are common in diabetes causing greater cardiovascular risks. Leukocytosis is a major marker of metabolic syndrome. Both neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are related to subclinical inflammation worsening the glycemic control. HbA1c is used as a marker of blood glucose regulation. OBJECTIVE: To investigate the association of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio with blood glucose regulation in patients with type 2 diabetes mellitus. METHODS: This comparative analytical study was conducted in Shifa International Hospital on diabetic patients. Sample size was calculated as 62 by WHO sample size calculator . Non randomized convenient sampling was used. Patients were divided into two groups according to HbA1c level taking 7% as cut off point. Full blood count, lipid profile and liver profile were carried out. Data was analyzed by SPSS version 21. Descriptive statistics were calculated for categorical variables. For quantitative normal and dispersed variables, independent student t and Mann Whitney U test were applied respectively. P Value less than 0.05 was considered significant. RESULTS: Out of total 93 patients,33 (35.4 %) were males and 60(64.5%) were females. The mean duration of disease was 8.26 ± 5.8 years. NLR and PLR were elevated in patients having poor glucose control but that difference was not significant. Significant difference between the groups was found with random blood glucose. LDL, triglycerides , cholesterol ratio, ALT and AST were raised in patients having poor glycemic control. CONCLUSION: Patients having poor blood glucose regulation have increased levels of haematological and serological parameters posing greater cardiovascular health risks to patients with type 2 diabetes